Tourism impact on quality of life in villages off the coast of Oman - Ali Manzam Ismailpor (تحقیقات کاربردی علوم جغرافیایی)
Tourism plays an important role in rural development. Tourism while enhancing the rural development process through diversification of economic activities, maintaining social integrity, environmental protection, and positive spatial-physical changes in rural settlements can increase the quality of life in rural areas. Due to the importance of this issue, in the present study, the effects of tourism on improving the quality of life of rural settlements were investigated. The present research is descriptive-analytical in terms of purpose and method. The data collection tool was a questionnaire and interviews with rural households. The statistical population includes rural settlements on the shores of the Oman Sea in the south of Sistan and Baluchestan province, the two coastal cities of Konarak and Chabahar (N = 4855). Using Cochranchr('39')s formula and quota sampling method, 356 samples in 12 villages that had tourist attractions were selected as a sample. Descriptive tests, analysis of variance and path analysis model were used to analyze the data and answer the research questions. The results of analysis of variance showed that tourism has a good linear relationship with increasing the quality of life in rural settlements of Konarak and Chabahar. So that according to the route analysis model, rural tourism has different and favorable effects on economic, social, environmental and physical-spatial indicators and the value of p of all Lamda parameters in the above model indicates the confirmation of all regression relationships. Among the four dimensions, tourism development has had the greatest effect on the economic dimension of quality of life and the least effect on the social dimension of quality of life in rural settlements.